12-O-Tetradecanoylphorbol-13-acetate Promotes Breast Cancer Cell Motility by Increasing S100A14 Level in a Kruppel-like Transcription Factor 4 (KLF4)-dependent Manner - He, Huan (American Society for Biochemistry and Molecular Biology, 2014)
The S100 protein family represents the largest subgroup of calcium binding EF-hand type proteins. These proteins have been reported to be involved in a wide range of biological functions that are related to normal cell development and tumorigenesis. S100A14 is a recently identified member of the S100 protein family and differentially expressed in a number of different human malignancies. However, the transcriptional regulation of S100A14 and its role in breast cancer needs to be further investigated. Here, we determined that 12-O-tetradecanoylphorbol-13-acetate (TPA) up-regulated the expression of KLF4 and facilitated its binding directly to two conserved GC-rich DNA segments within the S100A14 promoter, which is essential for the transactivation of KLF4 induced S100A14 expression. Furthermore, stable silencing of KLF4 significantly suppressed breast cancer cell migration induced by TPA. Collectively, these results offer insights into the fact that TPA provokes cell motility through regulating the expression and function of S100A14 in a KLF4-dependent manner.